A study of the degradation of compatibilized and uncompatibilized peanut shell powder/recycled polypropylene composites due to natural weathering. Issue 4 (29th July 2015) - Zaaba, Nor Fasihah; Ismail, Hanafi; Jaafar, Mariatti
Abstract : Compatibilized and uncompatibilized composites containing various loadings of recycled polypropylene (RPP) and peanut shell powder (PSP) were prepared. An amount of 3 parts by weight per hundred parts of resin of poly(ethylene‐ co ‐acrylic acid) (PEAA) was used as a compatibilizer in the RPP/PSP composites. The effect of PEAA and PSP loading on natural weathering was investigated. Composites without PEAA were used as a control, with the samples being tested before exposure to the environment. The PSP loading was varied from 0 to 40 wt%. The samples were exposed to natural weathering in the northern part of Malaysia for 6 months. The results showed that there was a higher decrease in tensile strength and elongation at break in the uncompatibilized composites compared with the compatibilized composites after exposure. Moreover, the tensile modulus increased for both the uncompatibilized and the compatibilized composites after natural weathering. The weight loss for both the uncompatibilized and the compatibilized RPP/PSP composites with PSP loading of 40 wt% after 6 months exposure was 9.24 and 7.13 wt%, respectively. J. VINYL ADDIT. TECHNOL., 23:290–297, 2017. © 2015 Society of Plastics Engineers